Stability & dispersibility of single-walled carbon nanotubes in suspensions of biopolymers chitosan, chondroitin sulphate & ocarboxymethylchitosan. - Tan, Tina Yu Qian. (2009)
The aim of this project was to investigate the dispersibility and stability of three different biopolymer suspensions in suspending single-walled carbon nanotubes (SWNTs). The SWNT-dispersant suspension was observed over a time period of one month under different temperatures and standing time. Dispersibility refers to the amount of SWNTs suspended while stability refers to the time span the SWNTs are suspended as individual entities in the dispersant. The three biopolymers used in this project are Chitosan (CTS), Chondroitin Sulphate (CS) and O-carboxymethylchitosan (OC). For comparison purposes, two other widely used surfactants that have been reported to display excellent dispersibility are also included in this project. They are sodium dodecylbenzene sulfonate (SDBS) and Triton® X-100. SWNTs were dispersed in 1%w/v biopolymer or surfactant suspension by ultrasonication. Analysis was then carried out on the supernatant obtained from centrifugation of the resulting SWNTs suspensions. The quantitative method which uses ultraviolet visible near infra-red (UV-vis-NIR) spectroscopy was employed to evaluate the dispersibility and stability of the five biopolymers and surfactants. The relative dispersibility was obtained by comparing area ratios calculated within wavelength range 550nm~800nm from the spectroscopy data. In addition, photoluminescence (PL) of the SWNTs suspension was used as an affirmative evaluation method to UV-vis-NIR. Observation of changes in UV-vis-NIR spectroscopy was monitored for 1 month to ascertain the stability. Upon investigation over the length of the project, biopolymer CTS showed potential under certain conditions to disperse and suspend SWNT with stability. It exhibited results comparable to surfactant Triton® X-100. It also had better overall results on comparison with the other 2 biopolymer CS and OC. Both UV-vis-NIR analysis and PL of CTS exemplified this quality.